Rice Farmers’ Agrarian Dynamics, a Historical Perspective - Ahmad Choibar Tridakusumah; Adi Nugraha; Iwan Setiawan; Ganjar Kurnia (BHUMI: Jurnal Agraria dan Pertanahan, 2022)
Abstract: As the staple food of Indonesians, rice has become an economic and political commodity in the country. This study aims to analyze the agrarian dynamics of rice farmers from a historical perspective, focusing on studying how the agrarian change affected the rice production mode in the present situation. The historiography approach used to produce critical analysis was complemented by tracing literature studies, especially in West Java, one of the main rice producers in Indonesia. The results showed that the structure of land tenure and ownership in rice farming had undergone a fundamental change. The dynamics that appear in rice can be seen at the level of agricultural technology intervention and local and national policies, which have experienced changes due to pressure from the agricultural production input sub-system. This pressure led to a change in peasant institutions that shifted from informal to formal, which was not in line with the structure of land tenure and ownership, which was still dominated by petty commodity producers. Keywords: Agrarian dynamics, farmers, historical, paddy